The Impact of Repetitive Methods to Enhance Students' Pronunciation in The Post-Pandemic - Djuhari, Asy Rahmania; Faridah, Didih (Universitas Galuh, 2024)
The obstacles that students face when learning pronunciation in the post-pandemic becomes the topic of the present study. This study aims to explore the impact of repetitive methods on the pronunciation phenomenon that affects high school students to address this issue. The present study used a qualitative case study. To gather the data, first, a questionnaire was administered to 23 students of the tenth grade from one of the Islamic Senior High School in Ciamis. Then, interview was conducted to an English teacher and three students as representatives of three pronunciation levels. To address the problem, the purpose of this study is to investigate the impact of repetitive methods on the pronunciation phenomenon that appears in Islamic Senior High School students. This study explores the obstacles encountered, the possible causes of the obstacles, the state of English-speaking ability, and the use of repetitive methods in pronunciation learning based on the perspectives of students and the teacher. The findings of the study showed a significant positive impact experienced by students from the use of repetitive methods as seen from several statements, namely increased confidence, fluency, and memory related to the pronunciation they learned during the post-pandemic. In addition, this study provides new insights into the use of repetitive methods as a powerful method in improving students' English-speaking ability.